Surveying - McCormac, Jack (New Jersey : Prentice-Hall, 1999)
The purpose of this book is to provide an introduction to surveying in such a manner as to interest the students in the subject.
Chapter 1 Introduction -- Chapter 2 Introduction to measurements -- Chapter 3 Introduction to distance -- Chapter 4 Distance corrections -- Chapter 5 Electronic distance measuring instruments (EDMs) -- Chapter 6 Introduction to leveling -- Chapter 7 Differential leveling -- Chapter 8 Leveling, continued -- Chapter 9 Angles and directions -- Chapter 10 Measuring angle and directions with transits, theodolites, and total stations -- Chapter 11 Miscellaneous angle discussion -- Chapter 12 Travers adjustment and area computation -- Chapter 13 Computer calculations and omitted measurements -- Chapter 14 Topographic surveying -- Chapter 15 The global positioning system (GPS) -- Chapter 16 Geographic information systems -- Chapter 17 Construction surveying -- Chapter 18 Volumes -- Chapter 19 Land surveying or property surveying -- Chapter 20 Horizontal curves -- Chapter 21 Vertical curves -- Chapter 22 Surveying-The profession.
Includes index.
Keywords: SURVEYING